Influence of Parameters on the Excitation Power of Third Harmonic Brushless Hybrid Excitation Generator - Yonghong Xia; Jianxin Xu; Jinhui Hu; Yeguo Yu; Ying Chen; Jingming Zhang (Energies)
Hybrid-excited generators have a wide voltage regulation capability or a wide range of variable-speed constant-voltage output capability, providing a significant advantage in the new energy power generation field. To achieve the optimal design of brushless hybrid excitation synchronous generators with third harmonic excitation, it is necessary to grasp the influence of design parameters on excitation power accurately. Firstly, this paper elaborates on the structure and principle of the hybrid excitation synchronous generator. From the perspective of excitation power generation, the expression for excitation power in hybrid excitation generators has been derived, identifying the primary factors influencing excitation power, which include winding parameters, structural parameters, and magnetic circuit saturation. Secondly, qualitatively calculate the influence of the number of turns and arrangement, turns in rotor harmonic, air gap length, and thickness of the permanent magnet on the excitation power, which is verified by the electromagnetic field finite element method. The results showed that the use of full pitch and a moderate increase in turns, a decrease in air gap length, and an increase in the thickness of the permanent magnet can all increase the rotor excitation power. A brushless hybrid excitation synchronous generator prototype based on third harmonic excitation was developed, the correctness of theoretical analysis and calculation were verified by test results.